A specialised pollination system using nectar-seeking thynnine wasps in Caladenia nobilis (Orchidaceae) - Phillips, R.D.; Bohman, B.; Brown, G.R.; Tomlinson, Sean; Peakall, R. (WILEY, 2020)
Caladenia is a diverse Australian genus that is exceptional among orchids in having both species pollinated by food-seeking and sexually deceived insects. Here, we investigated the pollination of Caladenia nobilis, a species predicted to be food-deceptive due to its large, cream-coloured and apparently nectarless flowers. Pollinator observations were made using experimental clumps of flowers. Measurements of floral colour were undertaken with a spectrometer, nectar was tested using GC-MS, and reproductive success was quantified for 2 years. While C. nobilis attracted nine species of insect, only males of the thynnine wasp Rhagigaster discrepans exhibited the correct size and behaviour to remove and deposit pollen. Male R. discrepans attempted to feed from the surface of the labellum, often crawling to multiple flowers, but showed no evidence of sexual attraction. Most flowers produced little or no nectar, although some may provide enough sucrose to act as a meagre reward to pollinators. Floral colouration was similar to a related Caladenia species pollinated by sexual deception, although the sexually deceptive species had a dull-red labellum. Reproductive success was generally low and highly variable between sites and years. In addition to most visitors being of inappropriate size for pollinia removal, the lack of response to the orchid by several co-occurring species of thynnine wasp suggests filtering of potential pollinators at the attraction phase. Our discovery of a pollination strategy that may be intermediate between food deception and food reward raises the question, how many putatively rewardless orchids actually produce meagre amounts of nectar?.